CAM and the Phenomenology of Pain. Issue 1 (2006) - Hankey, Alex
Abstract : Many CAM modalities afford relief from pain, each in its own way, or according to its own terminology. Comparison of different CAM modalities results in a simple phenomenology of pain centered around the idea that pain may be associated with blockages of the flow of energy in the system of nadis /acupuncture meridians.